Factors Predicting Zakāh Compliance Behaviour in Indonesia - Mumuh Muhammad; Aas Nurasiyah; A. Jajang W. Mahri; Ram Al Jaffri Saad (International Journal of Zakat, 2022)
The objective of this study is to analyze factors which predict zakāh compliance behavior using attitude towards zakāh and intention to pay zakāh as independent variables. This study uses the theory of planned behavior (TPB) as a theoretical framework. Quantitative approach is used with partial least squares-structural equation modeling (PLS-SEM) as data analysis technique based on a questionnaire survey of 90 zakāh payers (muzakki) in Bandung which is one of the districts in Indonesia. Results show that attitude towards zakāh has a positive impact significantly on intention to pay zakāh and intention to pay zakāh has a positive impact significantly on zakāh compliance behavior. Zakāh compliance behavior is found to be not directly affected by attitude towards zakāh but indirectly affected through intention in paying zakāh. Therefore, the theory of planned behavior shows suitability in both theory and practice in the zakāh cases. The results of study are expected to contribute new insight for zakāh fund management, particularly in the majority-Muslim countries, through improving zakāh compliance behavior. All parties, especially government and zakāh institutions, should pay attention seriously to these variables to optimize zakāh collection in the future.